Dry sliding wear and friction performance of zirconium dioxide tribopairs - Bailey, Richard; Sun, Yong (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
Zirconium is an attractive engineering material due to its commendable temperature and corrosion resistance, coupled with excellent biocompatibility. Despite these merits, its industrial applicability is hindered by elevated wear and friction in tribological settings. Previous research has concentrated on unmatched pair contacts involving zirconium and alumina, primarily due to its exceptional hardness. However, there is a noticeable dearth of literature addressing the match pair contact condition for zirconium dioxide. To address the suboptimal tribological performance, thermal oxidation emerges as a promising and cost-effective method to enhance the mechanical and electrochemical properties of zirconium. In this study, we employed thermal oxidation to produce a 6 μm thick oxide layer in an air furnace at 650 °C for 6 hours. Subsequently, the resulting surface coating underwent tribological testing using a pin-on-disc tribometer against two distinct counterface materials: alumina and zirconium dioxide, within a dry, unlubricated environment. The findings reveal that match contact between zirconium dioxide tribopair is unfavorable, leading to elevated friction and wear rates. Consequently, this configuration should be avoided in dry contact situations characterized by high contact pressures. However, under lower contact pressures, the wear performance becomes acceptable. Furthermore, when combined with lubrication, this system may present potential applications in bio-tribological systems.